Systemic Inflammation and Lung Function Impairment in Morbidly Obese Subjects with the Metabolic Syndrome. (24th February 2013) - van Huisstede, Astrid; Cabezas, Manuel Castro; Birnie, Erwin; van de Geijn, Gert-Jan M.; Rudolphus, Arjan; Mannaerts, Guido; Njo, Tjin L.; Hiemstra, Pieter S.; Braunstahl, Gert-Jan
Abstract : Background . Obesity and asthma are associated. There is a relationship between lung function impairment and the metabolic syndrome. Whether this relationship also exists in the morbidly obese patients is still unknown. Hypothesis . Low-grade systemic inflammation associated with the metabolic syndrome causes inflammation in the lungs and, hence, lung function impairment. Methods . This is cross-sectional study of morbidly obese patients undergoing preoperative screening for bariatric surgery. Metabolic syndrome was assessed according to the revised NCEP-ATP III criteria. Results . A total of 452 patients were included. Patients with the metabolic syndrome (n = 293 ) had significantly higher blood monocyte (mean 5.3 versus 4.9, P = 0.044 ) and eosinophil percentages (median 1.0 versus 0.8, P = 0.002 ), while the total leukocyte count did not differ between the groups. The FEV1 /FVC ratio was significantly lower in patients with the metabolic syndrome (76.7% versus 78.2%, P = 0.032 ). Blood eosinophils were associated with FEV1 /FVC ratio (adj. B −0.113, P = 0.018 ). Conclusion . Although the difference in FEV1 /FVC ratio between the groups is relatively small, in this cross-sectional study, and its clinical relevance may be limited, these data indicate that the presence of the metabolic syndrome may influence lung function impairment, through the induction of relative eosinophilia.